2021
DOI: 10.30892/gtg.35211-657
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Business Responses to South Africa’s Covid-19 Pandemic Emergency

Abstract: The COVID-19 pandemic has compelled tourism businesses to rapidly adjust operations in newer and more resilient ways as firms have to change priorities and respond to challenges, including of shifts in consumer demand. Extant research on tourism business responses and adaptations to COVID-19 highlights the significance of organizational resilience and ability of businesses to respond to uncertainty. Using a qualitative approach this paper investigates tourism business responses in South Africa, seemingly the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 25 publications
4
37
0
Order By: Relevance
“…The above findings affirm with the available writing on the reactions of tourism businesses to COVID-19 (Rogerson et al, 2021;Giddy and Rogerson, 2021;Steriopoulos and Wrathall, 2021;Dillette and Ponting, 2021). This additionally ties into the devastation of the pandemic to livelihoods, as respondents in the current study (alongside others represented in literature) underscored the importance of the sector to job creation and economic development.…”
Section: Operational Strategiessupporting
confidence: 88%
See 1 more Smart Citation
“…The above findings affirm with the available writing on the reactions of tourism businesses to COVID-19 (Rogerson et al, 2021;Giddy and Rogerson, 2021;Steriopoulos and Wrathall, 2021;Dillette and Ponting, 2021). This additionally ties into the devastation of the pandemic to livelihoods, as respondents in the current study (alongside others represented in literature) underscored the importance of the sector to job creation and economic development.…”
Section: Operational Strategiessupporting
confidence: 88%
“…For instance, one respondent, a meetings planner explained that, 'So we were able to implement some immediate strategies to try and cut some overheads and try and just restrict the operating costs'. This came as a result of the economic losses resulting from both the national and international lockdown regulations (Haywood, 2020;Kuscer et al, 2021;Rogerson, 2021), which not only halted the operations of the MICE sector, but also caused much uncertainty around when this form of tourism would resume. In fact, the national lockdown measures of South Africa had begun with an initial 21 days where only essential services of the country were permitted to operate (Bama and Nyikana, 2021;Hemmonsbey et al, 2021;Nyawo, 2020).…”
Section: Operational Strategiesmentioning
confidence: 99%
“…In the case of ecotourism in Ghana Soliku et al (2021) point out that existing facilities are over-reliant on the international market and starting to pivot towards the promotion of domestic tourism. Certain parallels emerge with the results from South African research on the adaptive responses of local tourism businesses (Giddy and Rogerson, 2021;Rogerson, 2021;Rogerson et al, 2021).…”
Section: African Tourism Research Responses To Covid-19mentioning
confidence: 75%
“…For South Africa it is demonstrated that adaptation to the crisis has been challenging because of the financial distress experienced by tourism enterprises in the wake of minimal government support (Booyens et al, 2021). Adaptive responses included downsizing of businesses, including worker retrenchments, price-cutting and readjustments to attract the domestic market, limited initiatives towards product diversification, energetic social media marketing and, in the case of accommodation enterprises, the re-purposing of properties (Rogerson, 2021). A strengthening of local inter-enterprise cooperation has been an additional widespread response (Giddy and Rogerson, 2021;Rogerson, 2021).…”
Section: African Tourism Research Responses To Covid-19mentioning
confidence: 99%
See 1 more Smart Citation